Problem-Solving Strategies Among Culinary Arts Students in Community Colleges - Techanamurthy, Umawathy; Alias, Norlidah; Dewitt, & Dorothy (Journal of Technical Education and Training, 2018)
Culinary Arts is an area in Technical Vocational Education and Training (TVET) where students need to possess problem-solving skills besides having fundamental subject matter knowledge and hands-on skills required for the technical aspects of cooking. The key components for learning to solve problems are analogizing, modelling, reasoning causally, and arguing. The development of these strategies will assist students in completing numerous cognitive tasks. However, little research has been done which provide information on the level of these skills in the context of students at Community Colleges, particularly among Culinary Arts students. Drawing from a survey data, the paper examines problem-solving skills of 831 Culinary Arts students, most of whom were aged 18-24, from eleven Community Colleges offering Certificate in Culinary Arts Programme throughout Malaysia. The analysis results revealed that students had only medium level of problem-solving skills. The finding is of great significance as knowing the level of problem-solving skills of Culinary Arts students is essential before designing a suitable intervention for them. Specifically, the findings can be used to justify the design of new learning environments towards developing problem-solving skills more effectively.